Artificial Intelligence (AI) Literacy in Early Childhood Education: A Scoping Review - Solichah, Novia; Shofiah, Nurul (Universitas Islam Indonesia, 2024)
In the past decade, artificial intelligence (AI) literacy has become a primary focus in digital literacy education research. However, the use of AI in early childhood education remains largely unexplored, prompting experts to conduct a scoping review. This scoping review aimed to explore various forms of AI application in early childhood education, and to identify commonly used methods in this topic. The database searches for scientific articles covered the period between 2016 to 2023. Inclusion and exclusion criteria were established, focusing on reviews related to AI literacy and early childhood education. Electronic databases such as Scopus, EBSCO Sciences, Emerald, Sinta, and Science Direct were used from December 2023 to February 2024. From the total of 260 articles selected for this analysis, only 10 met the inclusion criteria and were reviewed. The results showed that most articles used learning media tailored to children’s developmental stages to enhance literacy. These included smart toys integrating AI technology, particularly speech synthesis, virtual reality, robots, KIERO, and chatbots. Qualitative methods were commonly adopted, although some research used experimental methods and literature reviews. In summary, the integration of AI literacy in early childhood education contributed significantly to the development of active learning interventions for children.